2008
DOI: 10.1109/tvlsi.2007.915434
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Cooling of Integrated Circuits Using Digital Microfluidics

Abstract: Thermal management is critical for integrated circuit (IC) design. With each new IC technology generation, feature sizes decrease, while operating speeds and package densities increase. These factors contribute to elevated die temperatures detrimental to circuit performance and reliability. Furthermore, hot spots due to spatially nonuniform heat flux in ICs can cause physical stress that further reduces reliability. While a number of chip cooling techniques have been proposed in the literature, most are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 27 publications
0
54
0
1
Order By: Relevance
“…For higher dimensional matrix, the electrical wiring for the control electrode array has to be buried under another insulating layer. Interestingly, Paik et al have reported a similar configuration using two exposed grounding rails by the wayside [24]. However, doing so makes the fabrication process more complex because the reference electrodes require an additional insulating layer for the electrical wiring or throughhole interconnection between control electrode array and contact pads.…”
Section: Resultsmentioning
confidence: 99%
“…For higher dimensional matrix, the electrical wiring for the control electrode array has to be buried under another insulating layer. Interestingly, Paik et al have reported a similar configuration using two exposed grounding rails by the wayside [24]. However, doing so makes the fabrication process more complex because the reference electrodes require an additional insulating layer for the electrical wiring or throughhole interconnection between control electrode array and contact pads.…”
Section: Resultsmentioning
confidence: 99%
“…The use of electrowetting facilitates control of the surface area that is cooled by the liquid ribbon. Discrete droplet systems, such as those described by Kumari and Garimella [13] and others [12,15], have the capacity to dissipate heat fluxes an order of magnitude higher by implementing high frequency actuation of droplets across a heated surface; the device described in the present work is suited for applications where moderate heat dissipation is required over an area that varies temporally. Latent energy-based based systems can reach this level of heat dissipation, but must rely on suitably high surface temperatures to facilitate nucleate boiling as in Ref.…”
Section: Practical Implementationmentioning
confidence: 99%
“…Most prior work has focused on utilizing the sensible heating of droplets to remove heat from a surface [11][12][13][14][15]. In a typical configuration, an array of individually addressable electrodes moves a droplet to the desired location, where it absorbs heat and is subsequently removed and replaced by a cool droplet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, direct manipulation of discrete droplets enables fabrication and operation of highly automated microfluidics systems with more flexibility and higher efficiency [6][7][8][9][10][11][12]. Due to these unique advantages, EWOD digital microfluidics has been used for tremendous applications such as medical [13][14][15][16][17][18][19], display [20,21], optics [22,23], and cooling [24,25]. In addition, there are many recent EWOD studies on engineering applications such as optofluidics and solar energy [26,27].…”
Section: Introductionmentioning
confidence: 99%